PENGARUH STRUKTUR ASET, PERTUMBUHAN PENJUALAN DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN HUTANG (Studi pada perusahaan Pertambangan sub sektor batubara yang terdaftar pada Indeks Kompas 100 periode 2013-2018) - Jombrik TPR (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
This study aims to determine the effect of asset structure, sales growth, and managerial ownership on debt policy. This research was conducted at companies in the coal sub-sector mining sector. The analytical method used in this research is multiple linear regression. The results of the research on asset structure have a positive and significant effect on debt policy, sales growth does not have a significant effect on debt policy and managerial ownership has no significant effect on debt policy in the coal mining sub-sector companies. The three variables of asset structure, sales growth, and managerial ownership simultaneously have a significant effect on debt policy in the coal mining sector sub-sector, which means that these three variables are considered by companies in making debt policies.